2019
DOI: 10.1080/03079457.2019.1612852
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of suspected Newcastle disease (ND) outbreaks in Egypt uncovers a high virus velogenic ND virus burden in small-scale holdings and the presence of multiple pathogens

Abstract: Highly contagious Newcastle disease (ND) is associated with devastating outbreaks with highly variable clinical signs among gallinaceous birds. In this study we aimed to verify clinical ND suspicions in poultry holdings in Egypt suffering from respiratory distress and elevated mortality, comparing two groups of ND-vaccinated poultry holdings in three governorates. Besides testing for Newcastle disease virus (NDV), samples were screened for infectious bronchitis virus (IBV) and avian influenza virus (AIV) by RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…On the other hand, NDV-infected flocks are customarily diagnosed based on clinical signs, gross lesions of freshly dead birds and partial molecular amplification of F gene (200-500 bp) using specific primers for the region flanking F0 precursor cleavage site (Moharam et al, 2019). However, this strategy was found to be insufficient for detecting immune escape variants that emerge from the continuous immune pressure of LaSota vaccines, which explains the reason for sequencing the complete F gene in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, NDV-infected flocks are customarily diagnosed based on clinical signs, gross lesions of freshly dead birds and partial molecular amplification of F gene (200-500 bp) using specific primers for the region flanking F0 precursor cleavage site (Moharam et al, 2019). However, this strategy was found to be insufficient for detecting immune escape variants that emerge from the continuous immune pressure of LaSota vaccines, which explains the reason for sequencing the complete F gene in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of these antigenic epitopes in isolates from the current study and previously established isolates of different subgenotypes in Egypt showed that all these F neutralizing epitopes are highly conserved among our isolates, with one common amino acid substitution (K78R) detected. Interestingly, two old strains NDV-EG-35-2014 and NDV-KFR-B7-2012 showed an additional substitution at D170N; a recent isolate, found in both backyard birds and commercial vaccinated chickens (Moharam et al, 2019), showed a novel, uncommon amino acids substitution, V168I, that had not been previously detected (Table 2).…”
Section: Genetic Analysis Of F Neutralizing Epitopesmentioning
confidence: 90%
See 1 more Smart Citation
“…MH899939; genotype VII.1.1) was isolated from an ND vaccinated layer ock in Egypt suffering respiratory distress. The virus was characterized as velogenic having an intracerebral pathogenicity index (ICPI) of 1.8 and belonged to genotype 2.VIIb [35]. Pigeon type paramyxovirus-1 (pigeon/Germany/R75/1998), genotype 2.VI, was derived from the repository of the ND reference laboratory (Acc.…”
Section: Methodsmentioning
confidence: 99%
“…The phylogenic analysis of AOAV-1 strains circulated in small-scale poultry holdings in Egyptian villages revealed them belonging to genotype VIIb. Also, the viral transmission occurred among neighboring farms over long distances, and co-infections with multiple pathogens were identified [ 14 , 15 ]. Circulating AOAV-1 in wild birds in borderline or frontier Egyptian provinces containing wetlands was recorded [ 16 ].…”
Section: Introductionmentioning
confidence: 99%